(untitled) (International Journal of Engineering Management Science, 2021)
The construction industry in India is an important sector due to its enormous contribution to the country’s economic development. However due to the geographical, political, social and financial situation of the country, many construction projects are prone to delay. These delay factors can only be avoided by first identifying the factors and their sources. The main aim of this research was to find out the main causes of delay in Construction projects in India. The research design was quantitative, where the data was collected from clients, consultants and contractors using questionnaires. The questionnaire that was prepared with Google form technology, had a list of delay causing factors of which the respondents were ask to rank each according to the 5 point Likert scale. The data obtained were analyzed using the Statistical Program for Social Scientists (SPSS).The results obtained indicate that the top major causes of delay were; the shortage of materials, inaccurate time estimation, and errors during construction. In addition, the top major effects of delay were; Cost overrun, time overrun, negative social impacts and litigation. Also the top major risks associated with construction delay were; too much pressure on project stake holders, disputes amongst project participants, project abandonment, overall cost increase and decline in revenue.